Growth And Development Of Movement In Early Childhood Movement Learning Model - Panjaitan, Angel Naumora; Ginting, Reny Haganta; Siahaan, Stepanus Cristian H; Hutabalian, Ferdinan; Supriadi, Amir (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This research aims to produce a basic movement learning model for children aged 2-4 years. The basic movement learning model is tailored to the aspects of growth and development as well as the characteristics of children at this age, packaged through physical activities focused on basic locomotor, non-locomotor, and manipulative movements. The method used in this study is development with seven stages, namely: (1) collecting research results and information, (2) analysis of the product to be developed, (3) developing the initial product, (4) expert validation, (5) small-scale trials and revisions, (6) large-scale trials and revisions, and (7) creating the final product. The subjects of this research are children aged 2-4 years. The result of this research is a basic movement learning model for children aged 2-4 years that includes seven movement activities, namely: (1) Crawling and Creeping, (2) Walking on a Rope, (3) Throwing Bean Bags i nto Hoops, (4) Bowling Games, (5) Parachute Games, (6) Climbing, and (7) Jumping and Hopping. The conclusion is that the learning model developed is very appropriate for the characteristics as well as the growth and development of children aged 2-4 years and is suitable for basic movement learning in Playgroups.